2019
DOI: 10.1017/s0033291719002356
|View full text |Cite
|
Sign up to set email alerts
|

Using resting-state intrinsic network connectivity to identify suicide risk in mood disorders

Abstract: BackgroundLittle is known about the neural substrates of suicide risk in mood disorders. Improving the identification of biomarkers of suicide risk, as indicated by a history of suicide-related behavior (SB), could lead to more targeted treatments to reduce risk.MethodsParticipants were 18 young adults with a mood disorder with a history of SB (as indicated by endorsing a past suicide attempt), 60 with a mood disorder with a history of suicidal ideation (SI) but not SB, 52 with a mood disorder with no history … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
8
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(12 citation statements)
references
References 88 publications
4
8
0
Order By: Relevance
“…These results partly confirm findings from the few previous studies that have used ALFF to map the brains of depressed patients with a past history of SA and reported significantly lower ALFF values in the lateral PFC and occipital cortex in suicide attempters compared to depressed controls 19 . Consistent with DC results from the current study, a recent study reported decreased functional connectivity in depressed patients with SA in contrast to patients with SI and to patient controls without SI and past SA in several frontoparietal regions, including the right DLPFC/VLPFC and the right precuneus 39 .…”
Section: Discussionsupporting
confidence: 91%
“…These results partly confirm findings from the few previous studies that have used ALFF to map the brains of depressed patients with a past history of SA and reported significantly lower ALFF values in the lateral PFC and occipital cortex in suicide attempters compared to depressed controls 19 . Consistent with DC results from the current study, a recent study reported decreased functional connectivity in depressed patients with SA in contrast to patients with SI and to patient controls without SI and past SA in several frontoparietal regions, including the right DLPFC/VLPFC and the right precuneus 39 .…”
Section: Discussionsupporting
confidence: 91%
“…Nevertheless, fMRI studies show changes in functional networks, mainly SN, DMN, and VAN, in the context of systemic inflammation. These changes might explain some phenotypical phenomena, such as mood disorders and psychotic manifestations [283][284][285]. Finally, Goodkind et al (2015) found an overarching pattern of reduced gray matter volume in the bilateral insula and dorsal-anterior cingulate cortex-roughly corresponding to the SN, as well as correlated these changes with poorer executive functioning [286].…”
Section: Discussionmentioning
confidence: 92%
“…In addition to the frontal and temporal cortices, it is agreed that dysfunction associated with the parietal cortices is also implicated in the suicidal brain. Fronto-parietal network is involved as a part of cognitive control network which is critical for problem-solving and executive functioning [14]. Previous in vivo and post-mortem neurobiological studies have also implicated ventromedial and parietal regions in suicide risk [45].…”
Section: Discussionmentioning
confidence: 99%
“…To better understand the neural mechanisms underlying resting-state brain functions, there have been a shift in brain mapping from the study of discrete functional regions to the identification of networks [12]. The existed evidence for resting-state network (RSN) changes in SA comes largely from functional magnetic resonance imaging (fMRI) [13][14][15]. For example, suicide attempters with MDD have been demonstrated with synchronous alterations in intrinsic activity of the frontal, temporal, and parietal areas [16], altered intra-and inter-network connectivity among default mode network and salience network, as well as the right frontal-parietal network [17].…”
Section: Introductionmentioning
confidence: 99%